Analysis of Youtube Utilization in Learning Mathematics in the Pandemic Time of Covid-19 - Armiati; Okta Vutri Nupus (Rangkiang Mathematics Journal, 2022)
The Covid-19 pandemic is sweeping the entire world, including Indonesia, which has resulted in changes to the education system. Face-to-face learning system turns into online learning. Teachers are asked to be creative in using online learning media to achieve learning objectives, one of which is YouTube. This study aimed to analyze the use of YouTube as a medium for learning mathematics during the Covid-19 period. This research is a descriptive study through observation and interviews with teachers and students. The research instrument used student observation sheets, teacher observation sheets, and interview guides. The study results were obtained through descriptive analysis and show that YouTube has significant benefits as a medium for learning mathematics and as the best information seeker during the Covid-19 pandemic.